On Summability of Spectral Expansions Corresponding to the Sturm-Liouville Operator - Alexander S. Makin (International Journal of Mathematics and Mathematical Sciences, 2012)
We study the completeness property and the basis property of the root function system of the Sturm-Liouville operator defined on the segment [0, 1]. All possible types of two-point boundary conditions are considered.